Implementasi Strategi Funneling untuk Iklan Lembaga Amil Zakat di Facebook - Sholikul Isnaini; Muh. Nashirudin; Fairuz Sabiq (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2022)
Amil zakat fundraising institutions have a challenge because the law in Indonesia adheres to a voluntary system that cannot force prospective muzakki to pay zakat. On the other hand, society continues to question the high gap between the potential of zakat and the realization of its collection. It means zakat amil has to be more creative in developing marketing strategies. As an institution that operates both b-to-b and retail at once, amil zakat institutions should be able to take advantage of advertisements in online media such as Facebook. Funneling is very effective in conventional business. Unfortunately, it has not been used in many amil zakat institutions promptly. Based on data obtained, boosted posts with sponsored ads are hard selling or education about ziswaf services without collecting a database of prospective muzakki. This study is a qualitative study aimed at describing how the funneling strategy is applied to the products and services of the amil zakat. Although the ad sample was taken from Facebook, the ad flow design offered applied to other advertising media. The advertising flow was not trial as in the RND research. This design was used to strengthen the explanation regarding the application of funneling in zakat institutions. The results showed that the zakat amil must prepare a lead magnet to attract the attention of prospective muzakki to join the database management available. After prospective muzakki are in the database, zakat amil can follow up with them with various offers and education about zakat products and services and other ziswaf products.